Canada–AU human rights engagements: a TWAIL perspective. Issue 3 (2nd September 2022) - Bawa, Sylvia; Okafor, Obiora Chinedu
ABSTRACT: Despite the problematique of Global North/South relationships, human rights require transnational collaboration to successfully protect vulnerable people in the world. In particular, human rights engagements between Africa and the West are cemented in legacies of colonialism and mediated by development discourses that portray the continent as a paragon of poverty, corruption and backwardness. Within this context, we explore how an African Union (AU) human rights instrument could impact or transform Africa's transnational human rights engagements. Specifically, we use Canada–Africa human rights engagements as a starting point and basis for analysing the nature, orientation and impacts of such engagements (especially over three salient issues). Situating Canada as allegorical for the West, our findings show that Canadian human rights actors are critical of colonial legacies, have faith in the AU's leadership, and see the African Human Rights Action Plan as a potentially transformative instrument in human rights engagements in Africa.